Recovery of Murine Leukemia Virus from Large Volumes of Freshly Harvested Culture Fluids by Using a Single Density Gradient - Sottong, P. (1975)
Concentration and purification of murine leukemia virus for use as complement fixation antigens was accomplished by using a single density gradient in the model RK ultracentrifuge.